Programe-se : uma proposta de experimentação transmídia - Briglia, Tcharly Magalhães; Reis Junior, Dilson Alves de Souza; Piantavinha, Tainan Maria Barbosa de Souza; Barreto, Betânia Maria Vilas Bôas (Editus - Editora da UESC, 2018)
The work presents the production process and the theoretical research of the PROGRAME-SE project, a proposal for transmedia experimentation unfolded in a documentary, a webseries and an e-book. The project focuses on the analysis of the impacts of media convergence on language and content production for Brazilian television, as well as on the behavior of contemporary audiences. The discussions provide an overview of trends and prospects for the future of television amid the rise of other media.